Pengaruh Whistleblowing System Dan Budaya Organisasi Terhadap Pencegahan Kecurangan Di Kantor Imigrasi Kelas I TPI Bandung - Yulientinah, Dewi Selviani; Mukhlisha, Vidya Haifa (Universitas Logistik dan Bisnis Internasional, 2024)
Immigration Office Class I TPI (Immigration Checkpoint) Bandung is a government unit under the Ministry of Law and Human Rights and holds a substantial significance in the administration of immigration affairs and supervision services. Immigration office has a form of supervision to prevent all forms of fraud or violations in the form of whistleblowing systems and supervision in the form of attitudes and rules of